PERFORMANCE ANALYSIS OF RICIAN FADING CHANNELS USING M-PAM MODULATION SCHEME IN SIMULINK ENVIRONMENT (International Journal of Engineering and Computer Science, 2013)
In a wireless mobile communication system a signal can travel from transmitter to receiver over multipath reflective paths. This phenomenon, referred to as multipath propagation, can cause fluctuations in the received signal’s amplitude, phase, and angle of arrival, giving rise to the terminology multipath fading. When a strong stationary path such as a line of sight path is introduced into the Rayleigh fading environment, the fading becomes Rice-distributed fading. Ricean fading is suitable for characterizing satellite communications and in some urban environments. In this paper, the performance analysis of Ricean Fading Channels using M-PAM Modulation Scheme is implemented using Simulink tool.